IMPLEMENTASI STORYTELLING DIGITAL CANVA DALAM MATERI FATHU MAKKAH DI MI - Anjarwati, Anjarwati; Faridah, Anik; Putri, Ardelia Ananta; Rohmah, Faizahtur (Universitas Tanjungpura, 2025)
This study looks at how Madrasah Ibtidaiyah uses Canva-based digital storytelling to teach the Fathu Makkah content in Islamic Cultural History (SKI). This study's background stems from SKI's desire for more dynamic learning materials, boring teaching strategies, and low student engagement. The study examines how Canva facilitates digital storytelling as a learning innovation by analyzing books, journals, and pertinent papers using a qualitative library research method. The results demonstrate how Canva's incorporation of text, animation, audio, and visual components makes historical knowledge more interesting, comprehensible, and successful in assisting students in understanding moral principles like forgiveness and peace, which are represented in the Fathu Makkah event. While highlighting how this approach improves students' enthusiasm, engagement, creativity, and 21st-century abilities, the debate also identifies obstacles such inadequate facilities, differing instructor digital competencies, and time restrictions in media preparation. In conclusion, digital storytelling based on Canva has been shown to be successful in enhancing SKI learning and promoting significant, character-oriented Islamic teaching.